2008
DOI: 10.1128/jcm.01204-08
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of the Recombinant Capsid Protein of a Swine Norovirus into Virus-Like Particles and Evaluation of Monoclonal Antibodies Cross-Reactive with a Human Strain from Genogroup II

Abstract: Noroviruses (NoVs) are responsible for the majority of gastroenteritis outbreaks in humans. Recently, NoV strains which are genetically closely related to human genogroup II (GII) NoVs have been detected in fecal specimens from swine. These findings have raised concern about the possible role of pigs as reservoirs for NoVs that could infect humans. To better understand the epidemiology of swine NoVs in both the swine and the human populations, rapid immunoassays are needed. In this study, baculovirus recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 72 publications
1
27
0
Order By: Relevance
“…Baculoviruses were propagated in Trichoplusia ni High five cells (H5) grown in monolayer cultures at 28 °C in TNM-FH medium (Sigma-Aldrich), supplemented with 5% fetal calf serum (Gibco)60. Feline calicivirus (FCV), Urbana strain, kindly provided by K.Y.…”
Section: Methodsmentioning
confidence: 99%
“…Baculoviruses were propagated in Trichoplusia ni High five cells (H5) grown in monolayer cultures at 28 °C in TNM-FH medium (Sigma-Aldrich), supplemented with 5% fetal calf serum (Gibco)60. Feline calicivirus (FCV), Urbana strain, kindly provided by K.Y.…”
Section: Methodsmentioning
confidence: 99%
“…Our structural studies constitute a framework for the design of RHDV recombinant capsids as a delivery system for B and T cell epitopes (1,12), as high-resolution structures of viruses in the genus Lagovirus currently are not available. In addition to defining RHDV particle structure, our studies contribute to establishing the determinants of its assembly process.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-reactive MAbs have been described for noroviruses, and epitopes for most of them have been mapped within the most conserved regions of the norovirus capsid protein (C-terminal P or S domain). As suggested previously, cross-reactive MAbs could potentially be used in diagnostic assays (3,24,36,46,51); however, Oliver et al (45) described a cross-reactive MAb that recognized a linear epitope in the S domain of the VLPs from bovine noroviruses that did not detect native virions in fecal samples from experimental animals. They proposed that because the S domain forms the innermost domain of the capsid, the epitope is not accessible in native virions.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-reactive MAbs have been identified, and most of them have been mapped to the S domain or the C-terminal region of the P1 domain (3,4,35,45,46,51,65,66). It has been reported that certain MAbs block the interaction of VLPs with cells or synthetic HBGA (38,43), and two HBGA-blocking sites were recently mapped (11,37).…”
mentioning
confidence: 99%
See 1 more Smart Citation